Numerically controlled experiments on initial parameters for stress-sensitive reservoirs - Elemo, R. O.; Knapp, R. M. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper presents results of a study investigating the sensitivity of reservoir pressure to the parameters of stress-sensitive reservoirs. Stress-sensitive reservoirs are reservoirs with rock properties that depend on the effective stress on the reservoir rocks. The pressure sensitivity was studied by performing numerically controlled experiments in which the parameters of interest were varied, either singly or jointly, and the effect of the variations on the reservoir pressure was observed. A criterion function which characterized the difference between the calculated pressures using a certain parameter value and an assumed base value for the parameter was defined. The change of the criterion function as the parameters were varied was observed. A two-dimensional finite difference model of stress-sensitive geopressured-geothermal closed square reservoir saturated with a single-phase, slightly compressible fluid was used for the study. Single and two-parameter controlled experiments were performed on the initial formation permeability, porosity, uniaxial compaction coefficient, net pay thickness and the specific productivity index. The parametric calculations indicated that geopressured-geothermal reservoir pressure is sensitive to permeability, thickness, specific productivity index and uniaxial compaction coefficient, but porosity has little influence on calculated pressures.